A review of current surgical practice in the operative treatment of proximal humeral fractures: Does the PROFHER trial demonstrate a need for change?. Issue 5 (May 2016) - Dean, B. J. F.; Jones, L. D.; Palmer, A. J. R.; Macnair, R. D.; Brewer, P. E.; Jayadev, C.; Wheelton, A. N.; Ball, D. E. J.; Nandra, R. S.; Aujla, R. S.; Sykes, A. E.; Carr, A. J.
Abstract : Objectives: The PROximal Fracture of the Humerus: Evaluation by Randomisation (PROFHER) trial has recently demonstrated that surgery is non-superior to non-operative treatment in the management of displaced proximal humeral fractures. The objective of this study was to assess current surgical practice in the context of the PROFHER trial in terms of patient demographics, injury characteristics and the nature of the surgical treatment. Methods: A total of ten consecutive patients undergoing surgery for the treatment of a proximal humeral fracture from each of 11 United Kingdom hospitals were retrospectively identified over a 15 month period between January 2014 and March 2015. Data gathered for the 110 patients included patient demographics, injury characteristics, mode of surgical fixation, the grade of operating surgeon and the cost of the surgical implants. Results: A majority of the patients were female (66%, 73 of 110). The mean patient age was 62 years (range 18 to 89). A majority of patients met the inclusion criteria for the PROFHER trial (75%, 83 of 110). Plate fixation was the most common mode of surgery (68%, 75 patients), followed by intramedullary fixation (12%, 13 patients), reverse shoulder arthroplasty (10%, 11 patients) and hemiarthroplasty (7%, eight patients). The consultant was either the primary operating surgeon or supervising the operating surgeon in a large majority of cases (91%, 100 patients). Implant costs for plate fixation were significantly less than both hemiarthroplasty (p < 0.05) and reverse shoulder arthroplasty (p < 0.0001). Implant costs for intramedullary fixation were significantly less than plate fixation (p < 0.01), hemiarthroplasty (p < 0.0001) and reverse shoulder arthroplasty (p < 0.0001). Conclusions: Our study has shown that the majority of a representative sample of patients currently undergoing surgical treatment for a proximal humeral fracture in these United Kingdom centres met the inclusion criteria for the PROFHER trial and that a proportion of these patients may, therefore, have been effectively managed non-operatively. Cite this article: Mr B. J. F. Dean. A review of current surgical practice in the operative treatment of proximal humeral fractures: Does the PROFHER trial demonstrate a need for change? Bone Joint Res 2016;5:178–184. DOI: 10.1302/2046-3758.55.2000596.